Signs of the Wali Narratives at the Sacred Sites in Pamijahan, West Java - Christomy, Tommy (Islam in Southeast Asia, 2008)
In Signs of the Wali, Dr Tommy Christomy focuses on the one of the early founders of Islam on Java, Shakyh Abdul Muhyi, whose burial site at Pamijahan in Tasikmalaya is a place of contemporary ziarah. This study initially conceived of as a philological exploration of historical manuscripts has been transformed into a study of 'living manuscripts' - the contemporary narratives of the custodians at Pamijahan. As elsewhere in the Islamic world, tarekat and ziarah intersect in popular practice at Pamijahan. Dr Christomy explores this intersecting world, explaining the steps of his own research investigations that enfold as a journey of discovery as he proceeds. This investigation involves the search for traces of Tarekat Shattiriyyah in Pamijahan, given the pervasive presence of Tarekat Qadirriyah-Nashabandiyyah throughout Tasikmalaya. That Tarekat Shattiriyyah survives to this day is itself evidence of the tenacity that its historical roots have established in a particular place.